Sentiment Classification on The Act of Paedophiles on Twitter - Mohd Razali, Yasmin (IRC, 2019)
Twitter is an online microblogging site where people share their thoughts by tweeting on their timeline in short messages called tweets. Sometimes all the information shared by the user is not true. However, there are individuals who use Twitter for the satisfaction of their sexual desires. In this case, there are few cases for the past seven years of sex offenders logging in to Twitter to find their victims. This sex offenders are known as paedophiles. Paedophiles case have increased drastically in the social media since they are targeting children, especially when social media platforms are mainly used by children and teenagers. This paper aims to conduct a study on sentiment analysis that can predict the sentiment of the tweets that are posted by the users in twitter. Furthermore, the purpose of this project is to be able create a system with a new workflow in conducting a sentiment analysis. Although, there are a lot of researchers who came out with a few methods for sentiment analysis, this paper focuses mainly on doing a sentiment analysis classification on Twitter’s tweet based on the topic domain. Sentiment analysis uses a predicting sentiment polarity to get precise results. The main objective of this paper is to have a new workflow in doing sentiment analysis that uses KNIME platform and the data can be showed on the dashboard in Power BI. 4